Molecular Modelling and Structure Analysis of Lectins from Vigna linearis - Tripathi, Ankur; Roy, Nabarun (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted during the year 2022–2023 for in silico analysis of two Vigna linearis lectins in the computer lab, CDFT, Jodhpur, Rajasthan, India. Amino acid sequences of both lectins were obtained from NCBI database and analyzed using different computational tools. Primary structure analysis using ProtParam server revealed acidic, stable and hydrophobic nature of both VLL proteins. Both proteins were predicted heavily glycosylated with a single signal peptide cleavage site (A26-A27). High sequence similarity of both VLL proteins was observed with adzuki, rice bean and moth bean lectins. Both VLL proteins had high proportions of β-sheets in their secondary structure. Good quality 3D structures for both VLL proteins were modelled using Modeller software. A Jelly roll fold, also known as β-sandwich structure was identified in the 3D structure of both VLL proteins. Profunc server annotated both lectins as a carbohydrate binding regulatory protein with significant role in plant defense (GO terms: 0065007, 0006952, 0050896, 0006950, 0009607, 0030246). Galaxy Site web server predicted galactose, A2G (2-acetamido-2-deoxy-α-D-galactopyranose), MFU (Methyl α-L-fucopyranoside) and adenine as common binding ligands for both VLL proteins. Lig Plot analysis revealed hydrogen bonding and hydrophobic interactions were the major bonding interactions between VLL proteins and putative ligands. The results of the study would provide a base for conducting future research on Vigna linearis lectins for different applications.